Effect of Dietary Cholesterol, Phytosterol, and Docosahexaenoic Acid on Astaxanthin Absorption and Retention in Rainbow Trout - Yang Jin; Keshuai Li; Jon Olav Vik; Marie Hillestad; Rolf Erik Olsen (Aquaculture Nutrition)
Astaxanthin (Ax) determines the flesh redness of a salmonid fish which is the most desirable quality indicator by consumers. Fish cannot synthesize Ax de novo, therefore, the only way to increase flesh redness is to increase dietary input or improve the absorption and retention rate of dietary Ax. As a hydrophobic carotenoid, the absorption of Ax can be modulated by other lipid molecules in the diet. The present study explored the effect of three lipids, cholesterol (CH), phytosterol (PS), and docosahexaenoic acid (DHA) on Ax absorption, transport, and retention in rainbow trout. Dietary CH significantly improved Ax absorption by elevating plasma Ax levels (p<0.05); however, it had no effect on the whole body Ax or flesh color. Dietary PS appears to inhibit Ax absorption since fish had significantly (p<0.05) reduced whole body Ax. Dietary DHA appeared to have no effect on Ax absorption or retention. By comparing intestinal transcriptomes, a low density lipoprotein receptor (ldlr) gene was significantly downregulated in fish fed the CH diet as compared to the control diet. Since LDLR protein plays a major role in plasma lipoprotein turnover, we hypothesized that the inhibition of ldlr gene by high dietary CH resulted in higher retention of plasma Ax. The elevation of plasma Ax was not reflected in higher flesh coloration, which suggested other limiting factors governing Ax retention in the muscle. On the other hand, the transcriptomic and proteomic analyses found no changes of genes or proteins involved in Ax absorption, transport, or excretion in fish fed PS or DHA diets as compared to the control diet. In conclusion, this study has suggested that CH promotes Ax absorption by regulating lipoprotein retention and provide evidence for improving Ax absorption via dietary modulation.